EFEKTIVITAS COGNITIVE BEHAVIOR THERAPY UNTUK MENURUNKAN BODY SHAME - Riananda Regita Cahyani; Fathul Lubabin Nuqul (Universitas Islam Indonesia, 2019)
. Individuals who are unable to comply with the standards of ideal physical conditions found in the community are vulnerable to criticism or scorn. Criticism of the individual's physical appearance performed by other people and themselves tend to make individuals experience feelings of shame about their bodies. One of the factors that influence body shame is the thoughts individuals have about their physical condition. This study aims to determine the effectiveness of cognitive behavioral therapy to reduce the level of body shame. This research method uses quasi-experiments. The research subjects were 17 people. The experimental group was given Cognitive behavior therapy while the control group was given makeup skills training or Beauty Class. Data analysis used by using One-way ANOVA. The results showed that effective Cognitive Behavior Therapy to reduce the body shame level of research subjects compared to Beauty Class